Natural fiber substitution in glass fiber-reinforced plastics: A Tensile properties simulation - Wikarta, Alief; Andikusuma, Chandya; Ariatedja, Julendra; Batan, I Made Londen; Gapsari, Femiana; Khoo, Sze Wei (Universitas Negeri Padang, 2025)
Glass fiber-reinforced polymer composite materials, commonly used for industrial axial flow fan blades due to their high strength-to-weight ratio, are environmentally criticized for their non-biodegradability. This concern has prompted the investigation of eco-friendly alternatives, such as sisal and kenaf as natural fibers. Although they generally have lower mechanical properties than synthetic fibers, they offer advantages in terms of biodegradability, cost, and density. This study aims to evaluate the feasibility of partially substituting glass fiber with unidirectional natural fibers kenaf and sisal in a 14-layer GFRP axial fan blade through numerical simulation. The research employed a finite element method (FEM) to simulate tensile testing in accordance with ASTM D-638 standards. Several hybrid layer configurations were analyzed, focusing on the number and position of natural fiber layers replacing glass fiber, particularly the glass roving (GR) layers. The simulation investigated how these substitutions influence the overall tensile stress and elastic modulus of the composite blade structure. The findings suggest that this substitution does not significantly affect tensile characteristics but substantially improves the biodegradability of the composite, resulting in a more environmentally friendly material without compromising mechanical performance.